Pendapat Masyarakat tentang Efektivitas Penanganan Parkir Liar dalam Meningkatkan Pendapatan Asli Daerah Kota Medan - Nesya Ratri Pramudita; Hurian Kamela (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of the effectiveness of illegal parking management, policy effectiveness, and public opinion on the Original Local Revenue (PAD) of Medan City. The issue of illegal parking that has not been optimally addressed has the potential to cause parking fee leakage and hinder regional revenue growth. This study uses a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to 71 respondents and analyzed using validity tests, reliability tests, multiple linear regression analysis, t-tests, and determination coefficients. The results of the study show that the effectiveness of illegal parking management has a positive and significant effect on Medan City's Original Local Revenue. Policy effectiveness also proves to have a positive and significant effect on PAD. Meanwhile, public opinion does not have a significant effect on Original Local Revenue partially. Simultaneously, all independent variables affect Regional Original Revenue. This finding indicates that the increase in local revenue from the parking sector is more influenced by the effectiveness of policies and the implementation of illegal parking management than by public perception. Therefore, local governments need to strengthen supervision and policy consistency in parking management to optimize regional revenue.